Candida pericarditis: A rare case report - Malhotra, S.; Shweta, S.; K. Bhatia, N.J.; Suruchi, S.; Hans, C. (Health, Safety and Environment, 2020)
Fungal pericarditis is a rare entity especially in an immune competent host. Here we report a rare case of Candida albicans causing pericarditis in a 4 year old immune competent child. She presented with high grade fever and difficult breathing. The diagnosis was made by X ray Chest and confirmed by microbiological investigations on the drained pus material. The patient did not respond to surgical intervention and antimicrobial therapy and succumbed to her illness.